The Japanese Automotive Industry Model and Challenge for the Future? - Cole, Robert E. (Michigan Papers in Japanese Studies, 2020)
As the University of Michigan Center for Japanese Studies reflected on the deteriorating position of the domestic auto industry in the fall of 1980, and the strong competitive threat being posed by the Japanese automakers, we were struck by the extraordinary low quality of the public discussion of these critical issues. The national importance of the issues seemed only matched by the superficiality of the analyses being offered. The tendency to think in terms of scapegoats was particularly evident. The Japanese as the basic cause of our problems has been a particularly notable theme. To be sure, cooperation with the Japanese in formulating a rational overall trade policy may be an important part of the solution. It has also been fashionable to blame it all on American auto industry management for not concentrating on the production of small cars when "everyone knew" that was the thing to do. Alternatively, government meddling was blamed for all our problems. Clearly, the complex problem we faced required more penetrating analyses. It seemed therefore, that the time was ripe for a public seminar which moved beyond the rhetoric of the moment and probed some of the deeper causes of our problems and possible directions for future policy.